Pharmacoeconomics of pharmaceutical interventions related to dosage form in a hospital complex in southern Brazil - Bruna Dreyer ORTMANN; Tatiana Dourado HOFFMANN; Carine Raquel BLATT (Revista Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2023)
Objective: To identify and quantify the pharmaceutical interventions (PI) related to adequate dosage form and measure the actual and potential avoidable expenses. Methods: Cross-sectional study of quantitative approach with retrospective data collection for the year 2021, conducted in a hospital complex in Porto Alegre with 1089 hospital beds. The study included the PI of adequacy of dosage form to the prescribed dose and evaluated the drugs involved, the acceptability by the medical team and the financial impact. Data were exported from NoHarm.ai®️ and compiled into a Microsoft Office Excel®️ structured spreadsheet. The study was approved by the Ethics Committee of the institution under opinion no. 37227020.6.0000.5335. Results: During the study period, 634,547 prescriptions were written, of which 142,177 (22.41%) were evaluated by clinical pharmacists. From this evaluation, 4,918 PI were made, of which 432 (8.78%) referred to dosage form. After applying the selection criteria, 79 (18.29%) PI were excluded, resulting in 353 (81.71%). The analyzed FI were grouped into three outcomes: accepted 191 (54.11%), not accepted 151 (42.78%), and 11 (3.11%) not applicable. Among the 191 accepted interventions, 135 (70.68%) resulted in changing the dosage form of the prescribed drug, generating savings of US$6,553.97 per year for the institution and 56 (29.32%) resulted in reevaluation of the treatment leading to suspension of the drug. For the 151 unaccepted interventions, a potential savings of US$3,575,13 per year was estimated if the intervention was accepted. The drugs with the highest number of interventions were: enoxaparin (24.93%), ondansetron (21.37%) and methadone (11.24%). From another angle, the drugs that presented the greatest financial impact from the accepted interventions were: epoetin alfa (51.76%), morphine (19.08%) and enoxaparin (10.49%). Conclusion: Clinical pharmacist ajust drug dosage during prescription review over a one-year period accounted for approximately 9% of interventions and generated cost savings of $6,500, demonstrating the clinical and economic importance of prescription evaluation by the clinical pharmacist.